INVENTORY CONTROL USING STATISTICS FORECASTING ON MANUFACTURE COMPANY - Prasetio, Rizki Tri (Jurnal Informatika, 2014)
Abstract - Inventory Control is a main and the most crucial factor for company that can cause an efficient production process. A lot of research use different method to support inventory control. This research use several forecasting method such as, NaÃ¯ve Method, Exponential Smoothing, Exponential Smoothing with Trend, Moving Average, Weighted Moving Average and Linear Regression. Economic Order Quantity is used to calculate raw materials inventory. This research results suggest that company use Linear Regression as it has the smallest MAD and MSE of the six other methods. The company also has to implement Economic Order Quantity to minimalize loss profit due to excess inventory. Keywords : Inventory Control, Forecasting Method, Economic Order Quantity Abstrak - Pengendalian inventory merupakan salah satu faktor utama dan sangat penting bagi perusahaan karena sangat berpengaruh terhadap terciptanya proses produksi yang efisien. Banyak penelitian yang menggunakan beberapa metode guna mendukung pengendalian inventory. Penelitian ini menggunakan beberapa metode peramalan (forecasting method) diantaranya, NaÃ¯ve Method, Exponential Smoothing, Exponential Smoothing with Trend, Moving Average, Weighted Moving Average dan Linear Regression. Serta Economic Order Quantity (EOQ) yang digunakan untuk menghitung persediaan bahan baku yang dibutuhkan dalam proses produksi. Hasil penelitian menghasilkan bahwa metode peramalan Linear Regression memiliki tingkat kesalahan yang dihitung menggunakan MAD dan MSE paling kecil diantara 6 metode lainnya. Serta mengimplementasikan Economic Order Quantity untuk meminimalisir kerugian akibat kelebihan persediaan. Kata Kunci : Pengendalian Persediaan, Metode Peramalan, Economic Order Quantity